Britain’s Near Abroad - King, Anthony (The British Constitution, 2009)
Neville Chamberlain addressed the people of Britain a few days before he flew to Munich to meet Adolf Hitler in 1938. The subject of the prime minister was the dispute between the government of Czechoslovakia and the Sudeten German minority in that country. This dispute threatened to lead to a German invasion of Czechoslovakia and to engulf Europe in a war. Czech Republic and Slovakia, as well as Britain, became members of the European Union (EU). These three, along with the other members of the EU, started to have a voice in British domestic policy. The member states of the EU now form a basic part of the constitutional structure of the United Kingdom.